Hepatoprotectant Ursodeoxycholyl Lysophosphatidylethanolamide Increasing Phosphatidylcholine Levels as a Potential Therapy of Acute Liver Injury - Chamulitrat, Walee; Zhang, Wujuan; Xu, Weihong; Pathil, Anita; Setchell, Kenneth; Stremmel, Wolfgang (Frontiers in Physiology, 2012)
It has been long known that hepatic synthesis of phosphatidylchoine (PC) is depressed during acute such as carbon tetrachloride-induced liver injury. Anti-hepatotoxic properties of PC as liposomes have been recognized for treatment of acute liver damage. Ursodeoxycholate (UDCA) is a known hepatoprotectant in stabilizing cellular membrane. For therapeutic management of liver injury, we coupled UDCA with a phospholipid known as ursodeoxycholyl lysophosphatidylethanol-amide (UDCA-LPE). UDCA-LPE has been shown to first-in-class hepatoprotectant being superior to UDCA or PC. It inhibits mitochondrial damage and apoptosis, elicits survival signalling pathway, and promotes regeneration of hepatocytes. We herein report that a unique contribution of UDCA-LPE in increasing concentrations of PC in vitro and in vivo. UDCA-LPE-treated hepatocytes contained significantly increased PC levels. UDCA-LPE underwent the hydrolysis to LPE which was not the precursor of the increased PC. The levels of PC in the liver and blood were increased rapidly after intraperitoneally administration UDCA-LPE, and were found to be sustained even after 24 h. Among PC synthesis genes tested, UDCA-LPE treatment of mouse hepatocytes increased transcription of CDP-diacylglycerol synthase1 which is an enzyme catalyzing phosphatidic acid to generate intermediates for PC synthesis. Thus, UDCA-LPE as a hepatoprotectant was able to induce synthesis of protective PC which would supplement for the loss of PC occurring during acute liver injury. This property has placed UDCA-LPE as a candidate agent for therapy of acute hepatotoxocity such as acetaminophen poisoning.